KARAKTERISTIK FISIKOKIMIA DAN AKTIVITAS ANTIOKSIDAN SIRUP HERBAL BUAH PALA DENGAN PENAMBAHAN KARAGENAN RUMPUT LAUT - Inggriyani Usman; Rahim Husain; Shindy Hamidah Manteu (INASUA: Jurnal Teknologi Hasil Perikanan, 2026)
Nutmeg (Myristica fragrans Houtt.) is a spice that contains various bioactive compounds with antioxidant activity, making it a promising candidate for development into functional food products, such as nutmeg syrup. However, nutmeg syrup has low stability, so the addition of a stabilizer is necessary. Carrageenan, extracted from the seaweed Kappaphycus alvarezii, is known to act as a thickener and stabilizer in various food products. This study aimed to determine the effect of carrageenan addition on the physicochemical characteristics, antioxidant activity, and organoleptic properties of nutmeg syrup. The study used a non-factorial completely randomized design (CRD) with three levels of carrageenan concentration, namely P1 (0.50 g), P2 (0.66 g), and P3 (0.83 g), each with three replicates. The parameters observed included pH, viscosity, total soluble solids (°Brix), antioxidant activity (IC₅₀), and organoleptic properties. The results of the study showed that the addition of carrageenan had a significant effect (p<0.05) on viscosity, total dissolved solids, antioxidant activity, and the organoleptic parameter of thickness, but had no significant effect (p>0.05) on pH. Treatment P3 produced the highest viscosity of 166.56 ± 43.52 cP and the best antioxidant activity with an IC₅₀ value of 82.90 ppm (strong category), as well as the highest organoleptic viscosity score of 4.50 (the “very much like” category), while the highest total soluble solids were obtained in treatment P1 at 48.23 ± 0.35 °Brix. Based on the research results, treatment P3 (0.83 g carrageenan) was the best formulation because it produced the most favorable physicochemical characteristics, antioxidant activity, and organoleptic acceptance.